Multiple evanescent white dot syndrome presenting that as central serous chorioretinopathy - Demirok, Gülizar; Topalak, Yasemin; Nurözler Tabakçı, Burcu; Şengün, Ahmet (My University, 2019)
A 28-year-old man presented to the clinic with metamorphopsia, central scotoma, and visual loss in his right eye. After detailed ophthalmicexamination, fundoscopy showed localized elevation of the macula,and optical coherence tomography also showed subretinal serofi brinousaccumulation temporal to the fovea. He was evaluated as idiopathic central serous chorioretinopathy (CSCR). At the fi fth day of presentationhe was seen by the retinal consultant with fl uorescein angiography (FA) and indocyanine green angiography (ICGA) which were characteristicof multiple evanescent white dot syndrome (MEWDS) in the right eye. The diagnosis was changed as MEWDS presenting that as CSCR, andit was seen that the serofi brinous elevation began to decline after the fi rst week of presentation. Symptoms and visual disturbance recoveredwithout any further treatment at sixth month in this case.
Keywords: White Dot Syndrome; Multiple Evanescent; Syndrome